2014
DOI: 10.1165/rcmb.2013-0193oc
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine Dimethylaminohydrolase II Overexpression Attenuates LPS-Mediated Lung Leak in Acute Lung Injury

Abstract: Acute lung injury (ALI) is a severe hypoxemic respiratory insufficiency associated with lung leak, diffuse alveolar damage, inflammation, and loss of lung function. Decreased dimethylaminohydrolase (DDAH) activity and increases in asymmetric dimethylarginine (ADMA), together with exaggerated oxidative/nitrative stress, contributes to the development of ALI in mice exposed to LPS. Whether restoring DDAH function and suppressing ADMA levels can effectively ameliorate vascular hyperpermeability and lung injury in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 51 publications
4
71
3
Order By: Relevance
“…So, the effect of OCA on DDAH seems to depend on the etiology of cirrhosis, which is not only a novel finding, but again also might form a potential pitfall when going into clinical trial. Whereas we acknowledge that several researchers have demonstrated a DDAH-1-mediated reduction in ADMA upon FXR agonism, which we could not confirm in this study, for the time being, there is at least an equal amount of publications emphasizing either on the importance of DDAH-2 alone or combined with DDAH-1 with regard to ADMA metabolism, [5][6][7][8][9][10][11] leaving the solution to this puzzle unavailable at this time. To the point of "unprecedented" FXR agonism leading to DDAH-2 expression, we would like to draw the attention of Mookerjee et al to the article of Achan et al, 12 who found that all transretinoic acid, trough nuclear receptor binding, increased nitric oxide synthesis by endothelial cells in vitro through increased DDAH-2 gene expression and promoter activity.…”
contrasting
confidence: 67%
“…So, the effect of OCA on DDAH seems to depend on the etiology of cirrhosis, which is not only a novel finding, but again also might form a potential pitfall when going into clinical trial. Whereas we acknowledge that several researchers have demonstrated a DDAH-1-mediated reduction in ADMA upon FXR agonism, which we could not confirm in this study, for the time being, there is at least an equal amount of publications emphasizing either on the importance of DDAH-2 alone or combined with DDAH-1 with regard to ADMA metabolism, [5][6][7][8][9][10][11] leaving the solution to this puzzle unavailable at this time. To the point of "unprecedented" FXR agonism leading to DDAH-2 expression, we would like to draw the attention of Mookerjee et al to the article of Achan et al, 12 who found that all transretinoic acid, trough nuclear receptor binding, increased nitric oxide synthesis by endothelial cells in vitro through increased DDAH-2 gene expression and promoter activity.…”
contrasting
confidence: 67%
“…To evaluate whether MLCP activity has a barrier-protective and anti-inflammatory role in LPS-induced vascular barrier injury in vivo, we utilized a LPS murine model of ALI in conjunction with a lung-targeted gene delivery method which we have recently developed27. In this approach, commercial (Polyplus) cationic polymer jetPEI (polyethyleneimine) transfection reagent forms a complex with the DNA of interest that specifically targets the lungs with preferential localization to the endothelium27.…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, commercial (Polyplus) cationic polymer jetPEI (polyethyleneimine) transfection reagent forms a complex with the DNA of interest that specifically targets the lungs with preferential localization to the endothelium27. Utilizing this approach, plasmid encoding C/A MYPT1 1–300 or vector control (empty pcDNA 3.1) complexed with JetPEI was introduced intravenously (i.v.).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations